TEACHERS READINESS AND CHALLENGES IN INTEGRATING DIGITAL-ERA HISTORY LEARNING RESOURCES IN SENIOR HIGH SCHOOLS IN PALEMBANG: Kesiapan dan Tantangan Guru dalam Mengintegrasikan Sumber Belajar Sejarah Era Digital di SMA Palembang - sejarah, kabib sholeh@; Sukardi; Nur Azizah; Randoh Fernando (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to analyze the readiness and challenges of teachers in integrating local history materials as a source of learning history in the digital era in Palembang High Schools. Qualitative research methods with case study strategies, data collection includes in-depth interviews with history teachers, observations, questionnaires and analysis of curriculum documents. This approach allows for a comprehensive exploration of teachers' experiences, perceptions, and practices in integrating digital learning resources into history learning. Initial findings indicate that despite awareness of the potential of digital learning resources, teachers face various challenges in their implementation. Factors such as limited infrastructure, lack of adequate training, and limited understanding of Technological Pedagogical Content Knowledge (TPACK) are the main obstacles. In addition, this study also revealed a gap between teacher readiness and the demands of digital transformation in education. The implications of this study include the need for more targeted professional development programs to improve teachers' digital competence, improvements in technology infrastructure in schools, and curriculum adjustments that accommodate the integration of digital learning resources. The importance of institutional support in facilitating the transition to more interactive and technology-based history learning. In conclusion, despite significant challenges, the integration of digital learning resources in history learning in Palembang High Schools has great potential to improve the quality of education..